Venous Thromboembolism and Infection in a child with Nephrotic Syndrome: Dangerous interplay of Old enemies - Neha Bhandari; Suprita Kalra; Sheikh Muzaffar; Sanjeev Khera (Indian Journal of Child Health, 2021)
Venous thrombosis a known complication of Nephrotic syndrome. High IgE levels are commonly seen in children with Nephrotic syndrome. High IgE levels at the onset of Nephrotic syndrome with sepsis are risk factors for venous thromboembolism. We present through this a severe case of venous thromboembolism and sepsis in a child with Nephrotic syndrome.